2022
DOI: 10.1021/jacs.2c00847
|View full text |Cite
|
Sign up to set email alerts
|

Development of Organogels for Live Yarrowia lipolytica Encapsulation

Abstract: Encapsulation of cells/microorganisms attracts great attention in many applications, but current studies mainly focus on hydrophilic encapsulation materials. Herein, we develop a new class of hydrophobic and lipophilic organogels for highly efficient encapsulation of Yarrowia lipolytica, an oleaginous yeast, by a mild and nonsolvent photopolymerization method. The organogels allow free diffusion of hydrophobic molecules that oleaginous yeasts require to survive and function. Moreover, they are mechanically rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In short, the result of experiments showed the improvement of lipophilicity of rGO aerogel by organic coating (COF) from the macroscopic level. 44 On the one hand, during the preparation of composite organic PCM, the aerogel with better lipophilicity makes the molten PCM easier to fill the internal pores, especially those narrow micropores and mesopores. On the other hand, during the phase transition process of composite PCM, the surface with better affinity enables the molten PCM with better free movement in the micropores, thereby improving the crystallization behavior, which was reflected in XRD tests and the subsequent DSC analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the result of experiments showed the improvement of lipophilicity of rGO aerogel by organic coating (COF) from the macroscopic level. 44 On the one hand, during the preparation of composite organic PCM, the aerogel with better lipophilicity makes the molten PCM easier to fill the internal pores, especially those narrow micropores and mesopores. On the other hand, during the phase transition process of composite PCM, the surface with better affinity enables the molten PCM with better free movement in the micropores, thereby improving the crystallization behavior, which was reflected in XRD tests and the subsequent DSC analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It was a favorable condition for preparation of PEG-rGO-based composite PCMs. In short, the result of experiments showed the improvement of lipophilicity of rGO aerogel by organic coating (COF) from the macroscopic level . On the one hand, during the preparation of composite organic PCM, the aerogel with better lipophilicity makes the molten PCM easier to fill the internal pores, especially those narrow micropores and mesopores.…”
Section: Resultsmentioning
confidence: 99%
“…Conductive hydrogels with three-dimensional (3D) networks can be applied as substrates of flexible electronic devices, such as smart energy storage equipment, wearable and portable sensors, and soft robots, because of their high flexibility and adjustable conductivities. However, due to the inevitable freezing of the hydrogels and the sluggish electron and ion transport at low temperatures, , their ionic conductivity and flexibility reduce seriously, causing malfunction of the devices. Many efforts have been made to address this issue by weakening the hydrogen bonds between water molecules, including the modification of polymer networks and the introduction of antifreezing agents (ionic liquids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulating EMC in hydrogels to form the "living material". The hydrogel encapsulation EMC has many advantages: first, the hydrogel could provide water, which is necessary for the EMC survival; 23 second, the hydrogel was able to avoid the potential inhibitory effect of the epidermal environment on the EMC; finally, hydrogel prevented engineered bacteria from escaping into the environment. 24 In this study, it was demonstrated that the sucrose-secreting engineered S. elongatus was able to support the growth of commonly used microbial chassis (Lactococcus lactis and Escherichia coli) in the EMC.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Encapsulating EMC in hydrogels to form the “living material”. The hydrogel encapsulation EMC has many advantages: first, the hydrogel could provide water, which is necessary for the EMC survival; second, the hydrogel was able to avoid the potential inhibitory effect of the epidermal environment on the EMC; finally, hydrogel prevented engineered bacteria from escaping into the environment …”
Section: Introductionmentioning
confidence: 99%